2010
DOI: 10.1039/c0cc00956c
|View full text |Cite
|
Sign up to set email alerts
|

Anionic phthalocyanines targeting G-quadruplexes and inhibiting telomerase activity in the presence of excessive DNA duplexes

Abstract: Anionic phthalocyanines inhibited efficiently telomerase activity even in the presence of excess double-stranded DNA (dsDNA) because of their selective binding to telomere G-quadruplex, although low selectivity of a typical cationic ligand, TMPyP4, to the G-quadruplex allowed telomerase reaction under conditions with dsDNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 36 publications
3
77
0
Order By: Relevance
“…[1] Hemin is quite unique since it is one of the sparse examples (with NMM [23] and Cu-APC) [24] of an anionic small molecule that displays affinity for quadruplex DNA. [25] This explains why the replacement of hemin by another ironA C H T U N G T R E N N U N G (III) porphyrin (or other) candidate has not been investigated.…”
mentioning
confidence: 99%
“…[1] Hemin is quite unique since it is one of the sparse examples (with NMM [23] and Cu-APC) [24] of an anionic small molecule that displays affinity for quadruplex DNA. [25] This explains why the replacement of hemin by another ironA C H T U N G T R E N N U N G (III) porphyrin (or other) candidate has not been investigated.…”
mentioning
confidence: 99%
“…Unsurprisingly, the affinity binding constants of anionic quadruplex ligands are relatively small: Ka ~10 4 M -1 for phtalocyanines [138] and ~10 5 for NMM [132]. Nonetheless, the Ka of the interaction of Fe III -protoporphyrin IX (only one negative charge) and selected G-quadruplex DNA aptamer reaches Ka ~10 7 M -1 [135,141].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 94%
“…It is striking to note that negatively charged compounds such as Nmethylmesoporphyrin IX (NMM) [44,45,132,133], protoporphyrin IX [134], hemin (Fe IIIprotoporphyrin IX) [135][136][137] with two carboxylic groups or tetraphtalocyanines with four sulfonate groups [138][139][140] are endowed with G-quadruplex binding capability. Since negatively charged molecules are devoid of any affinity for double-stranded DNA due to strong electrostatic repulsion, negatively charged aromatic molecules that are able to undergo external stacking with a G-quartet have a chance to be G-quadruplex selective [138,140].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 98%
“…13a). 83 Although the affinity of this complex for human telomeric DNA is modest (2.4 Â 10 4 M À1 at 20 1C) its selectivity for quadruplex over duplex DNA is greatly enhanced. In the same study, it was also shown that this complex is able to inhibit telomerase (with EC 50 = 1.2 mM).…”
Section: 33mentioning
confidence: 99%